Contracts 'Not for the Public Good' and the Classical Law of Contract. Issue 1 (2nd January 2022) - Swain, Warren
ABSTRACT: During the nineteenth century, legal writers began to put the law of contract into a more rationale and ordered framework. This approach reached its apotheosis in the classical law of contract, which retains some influence in modern times. At its core was the belief that contracts were formed by a meeting of wills – that is, contracts were based on consent. Historically, however, there are instances where the law refused to enforce a contract even if the parties had seemingly freely consented to it. Two major examples were contracts that were against morality or public policy. Both of these categories evolved in the nineteenth century. They came to be seen as increasingly anomalous and restricted. They did not, however, disappear altogether.